Differences in Floral Scent and Petal Reflectance Between Diploid and Tetraploid Chamerion angustifolium - Palmqvist, Björn; Brazeau, Hannah A.; Parachnowitsch, Amy L. (Frontiers in Ecology and Evolution, 2021)
Genome duplication in plants is thought to be a route to speciation due to cytotype incompatibility. However, to reduce cross-pollination between cytotypes in animal-pollinated species, distinctive floral phenotypes, which would allow pollinator-mediated assortative mating between flowers, are also expected. Chamerion angustifolium is a Holarctic species that forms a hybrid zone between diploid and tetraploid populations in the North American Rocky Mountains. Extensive research has shown that these cytotypes differ in many ways, including some floral traits, and that pollinators can discriminate between cytotypes, leading to assortative mating. However, two signals commonly used by insect pollinators have not been measured for this species, namely petal colour and floral scent. Using greenhouse-grown diploids and tetraploids of C. angustifolium from the ploidy hybrid-zone in the North American Rocky Mountains, we show that both floral scent signals and petal reflectance differ between cytotypes. These differences, along with differences in flower size shown previously, could help explain pollinator-mediated assortative mating observed in previous studies. However, these differences in floral phenotypes may vary in importance to pollinators. While the differences in scent included common floral volatiles readily detected by bumblebees, the differences in petal reflectance may not be perceived by bees based on their visual sensitivity across the spectra. Thus, our results suggest that differences in floral volatile emissions are more likely to contribute to pollinator discrimination between cytotypes and highlight the importance of understanding the sensory systems of pollinators when examining floral signals.